EFFECT OF INOCULATION METHODS OF MESORHIZOBIUM (AKCR-1) ON YIELD ATTRIBUTES AND YIELD OF CHICKPEA (Journal of Plant Disease Sciences, 2025)
This study was conducted to assess the effect of inoculation method on nutrient uptake and yield parameters of chickpea during the 2024-25 season at Pulse Research Unit, Dr. PDKV, Akola. The experiment was laid out in randomized block design with three replications and it was comprising with eight treatments including uninoculated control and a recommended dose of chemical fertilizer with six treatments of different inoculation methods of Mesorhizobium by see treatment, soil application with FYM, soil application at sowing, 10, 20, 30 DAS. Field evaluation confirms that inoculation of Mesorhizobium (AKCR-1) @ 25 g/kg seeds and soil application @ 4 kg/acre in furrows at 20 DAS exhibited significant influence on the number of nodules at 45 DAS and nodule dry weight, yield Rabi Mesorhizobium attributes and yield among the all inoculated methods. The study helps to access the method of application as well as proper timing of the inoculation to be applied so as to increase the yield.
Keywords: Chickpea, Furrows, Inoculation methods, Mesorhizobium, Seed treatment, Soil application